The Challenges of Major Disasters in Algeria: An analytical approach to the public landscape in light of urban transformations - AZEB , Mohamed el Bachir; BOUZAHZAH , Foued (Journal of Human Sciences, 2024)
Due to its geographical location, Algeria faces numerous challenges in dealing with the increasing threats and complexities of major hazards and the consequences of disasters, particularly those of natural origin such as earthquakes, floods, landslides, fires, extreme heat waves, and droughts. These weather phenomena are exacerbated by global climate change, which also contributes to increased vulnerability and exposure to various crises, including urban accumulations and excesses. To address this situation, a comprehensive structured strategy with an effective approach at all levels is necessary. This strategy should include the development of sensing, prediction, and response capabilities, as well as the strengthening and adaptation of preventive measures and response mechanisms, rehabilitation of critical infrastructure, community outreach, and systematic planning mechanisms. These measures aim to prevent risks or minimize the impact and cost of disasters while achieving qualitative and sustainable development goals.